2009
DOI: 10.4315/0362-028x-72.4.853
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Microbiological Safety of Edible Roasted Nut Kernels on Retail Sale in England, with a Focus on Salmonella

Abstract: There is little published information on the prevalence of Salmonella in edible nut kernels. A study in early 2008 of edible roasted nut kernels on retail sale in England was undertaken to assess the microbiological safety of this product. A total of 727 nut kernel samples of different varieties were examined. Overall, Salmonella and Escherichia coli were detected from 0.2 and 0.4% of edible roasted nut kernels. Of the nut varieties examined, Salmonella Havana was detected from 1 (4.0%) sample of pistachio nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Similar studies have been undertaken to determine the prevalence and/or concentration of Salmonella in peanuts and tree nuts (9)(10)(11)(15)(16)(17). Danyluk et al (9) determined the prevalence of Salmonella in raw almonds to be 0.87% + 0.2% (81 of 9,274 samples), and the concentration was 1.2 to 2.9 MPN/100 g. In an outbreak investigation involving in-shell peanuts in Australia, Kirk et al (15) reported the concentration of Salmonella at 0.03 to ~2 organisms per g. In a 3-year survey of preroasted nut kernels (peanut, almond, cashew, hazelnut, and Brazil nut) in Australia, Salmonella was detected in a single raw almond sample (1 of 60 almond samples; 1 of 921 total samples) (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies have been undertaken to determine the prevalence and/or concentration of Salmonella in peanuts and tree nuts (9)(10)(11)(15)(16)(17). Danyluk et al (9) determined the prevalence of Salmonella in raw almonds to be 0.87% + 0.2% (81 of 9,274 samples), and the concentration was 1.2 to 2.9 MPN/100 g. In an outbreak investigation involving in-shell peanuts in Australia, Kirk et al (15) reported the concentration of Salmonella at 0.03 to ~2 organisms per g. In a 3-year survey of preroasted nut kernels (peanut, almond, cashew, hazelnut, and Brazil nut) in Australia, Salmonella was detected in a single raw almond sample (1 of 60 almond samples; 1 of 921 total samples) (11).…”
Section: Resultsmentioning
confidence: 99%
“…A similar 3-year study on retail-level nut kernels (peanut, almond, cashew, hazelnut, and Brazil nut) in Australia reported no Salmonella detected in 564 total samples (10). Several studies have surveyed edible nuts at retail sale in the United Kingdom for the presence of Salmonella (16,17). In 2008, 727 nut kernels of several varieties were examined, with Salmonella detected in only a single sample of pistachios (1 of 25 pistachio samples) (16).…”
Section: Resultsmentioning
confidence: 99%
“…Salmonellosis has been associated with consumption of contaminated almonds (8,20,22) and pine nuts (19), and Escherichia coli 0157:H7 infections have been associated with contaminated hazelnuts (9,25). These and other tree nuts have been reported to be occasionally contaminated with foodbome pathogens (8,10,14,15,23,24,30,32).…”
mentioning
confidence: 99%
“…Salmonella has been isolated from various tree nuts (16,24,29,30,37,38,44,46). The pathogen can survive in almond orchard soil for at least 5 years (48) and grow in soil containing almond hull nutrients (25).…”
mentioning
confidence: 99%